Structure–Activity and Stability Relationships for Cobalt Polypyridyl‐Based Hydrogen‐Evolving Catalysts in Water. Issue 22 (13th November 2017) - Schnidrig, Stephan; Bachmann, Cyril; Müller, Peter; Weder, Nicola; Spingler, Bernhard; Joliat‐Wick, Evelyne; Mosberger, Mathias; Windisch, Johannes; Alberto, Roger; Probst, Benjamin
Abstract: A series of eight new and three known cobalt polypyridyl‐based hydrogen‐evolving catalysts (HECs) with distinct electronic and structural differences are benchmarked in photocatalytic runs in water. Methylene‐bridged bis‐bipyridyl is the preferred scaffold, both in terms of stability and rate. For a cobalt complex of the tetradentate methanol‐bridged bispyridyl–bipyridyl complex [Co II Br(tpy)]Br, a detailed mechanistic picture is obtained by combining electrochemistry, spectroscopy, and photocatalysis. In the acidic branch, a proton‐coupled electron transfer, assigned to formation of Co III −H, is found upon reduction of Co II, in line with a p K a (Co III −H) of approximately 7.25. Subsequent reduction (−0.94 V vs. NHE) and protonation close the catalytic cycle. Methoxy substitution on the bipyridyl scaffold results in the expected cathodic shift of the reduction, but fails to change the p K a (Co III −H). An analysis of the outcome of the benchmarking in view of this postulated mechanism is given along with an outlook for design criteria for new generations of catalysts. Abstract : Cobalt HECs at work : Various cobalt polypyridyl hydrogen evolution catalysts (HECs) are benchmarked both by their photocatalytic and electrocatalytic performance in aqueous buffered media to substantiate the influence of pH on catalysis. Structure–activity relations are drawn, and the methyl‐bis‐bipyridyl scaffold emerges as the superior catalytic motif, both in terms of stability and rate of catalysis.